Sosialisasi Serta Pendampingan dalam Pembuatan Nomor Induk Berusaha ( NIB OSS-RBA) Kepada Pelaku UMKM di Desa Seberang Sanglar - Hendra Taufik; Andre Sugandha Hutapea; Ainun Maidiyah Wiranti; Azizah Yendra Shabihah; Elsa Viola; Erpan Halomoan Zebua; Fahira Ismail; Hanza Viola; Indrasari Simbolon; Muhammad Ferdiansyah Putra (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
In the era of free markets, Micro, Small, and Medium-Sized Enterprises (MSMEs) must fulfill specific conditions in order to compete. In order to help business actors—particularly craftspeople and MSME actors—better expand their enterprises, community service activities are necessary because many of them still lack business legitimacy. The purpose of this activity is to introduce the company Identification Number (NIB), which may be obtained online, and to raise awareness of the need of maintaining company licenses. The Indonesian government wants to make business actor registration easier by using the Online Single Submission (OSS) to submit NIBs. The provision of business legality theory and practice is part of this support. The purpose of this study is to arm business actors with information and expertise about creating NIB so they may grow their enterprises. The findings demonstrated that the community's comprehension of creating NIB, which each and every business actor must own, had improved. Because the NIB has granted legal status to the firm, it has made doing business simpler. MSME participants in Seberang Sanglar Village also benefit from protection from the government, easy access to financing, government empowerment, and support for their business growth.